The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0103-636x2012000200016
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem em Educação Matemática

Abstract: O final da década de 1970 marca o início da trajetória da Modelagem Matemática na educação matemática brasileira, em oposição, segundo a pesquisadora Lourdes Maria Werle de Almeida, ao Movimento da Matemática Moderna, como uma alternativa de se fazer matemática nas aulas de matemática e em outros espaços, e contrária à ideologia da certeza.Há diversas entradas para Modelagem Matemática, tanto no âmbito da Matemática Aplicada quanto na Educação Matemática. No contexto da Educação Matemática ela pode ser compree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The previous data record that the first articles published around our investigative region date from the 1990s and early 2000s, respectively, by Souza and Baldino (1995) and Baldino (2001). We note that these articles have the professor-researcher Roberto Ribeiro Baldino and the Grupo de Pesquisa-Ação em Educação Matemática [Research-Action Group in Mathematics Education] (GPA) in common.…”
Section: Research Groups In Mathematics Education As An Object Of Stu...mentioning
confidence: 87%
See 2 more Smart Citations
“…The previous data record that the first articles published around our investigative region date from the 1990s and early 2000s, respectively, by Souza and Baldino (1995) and Baldino (2001). We note that these articles have the professor-researcher Roberto Ribeiro Baldino and the Grupo de Pesquisa-Ação em Educação Matemática [Research-Action Group in Mathematics Education] (GPA) in common.…”
Section: Research Groups In Mathematics Education As An Object Of Stu...mentioning
confidence: 87%
“…Considering the number of studies, next, we recorded five articles in the A1-Micro classification. In these studies, the observed evidence corresponding to the parameters of the referred classification were mainly philosophical/epistemological discussions/questions, presentation of its organization, management of activities, operation, and entry regarding the GPA (Baldino, 2001); analysis of formative, learning, identity, and acquisition aspects of the scientific habitus about the functioning of the research group Educim (Teixeira, 2013;Teixeira et al, 2015); theoreticalmethodological discussions of the Ghoem on the lines of research "mapping the training and performance of teachers who teach/taught mathematics in Brazil" (Garnica, 2018) and "oral history, narratives, and teacher training: research and intervention" (Silva, 2018).…”
Section: Investigation Areas and Levels Of Methodological Approaches ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A Figura 1 apresenta o quantitativo de trabalhos por ano de publicação. Os dados supracitados registram que os primeiros artigos publicados em torno da nossa região investigativa datam da década de 1990 e início dos anos 2000, respectivamente, dos autores Souza e Baldino (1995) e Baldino (2001). Nota-se que esses artigos têm em comum o professor-pesquisador Roberto Ribeiro Baldino e o Grupo de Pesquisa-Ação em Educação Matemática (GPA).…”
Section: Temporalidade Dos Trabalhosunclassified
“…A dissertação de mestrado de Hermann (2011) também foi desenvolvida no e sobre o grupo de pesquisa em questão, e analisou como se dá a prática científica no interior do grupo, os estilos e os pensamentos coletivos. Os artigos de Souza e Baldino (1995) e Baldino (2001) também estavam vinculados à Unesp/RC à época de sua produção.…”
Section: Características Gerais Dos Trabalhosunclassified